PROBLEM ONTOLOGY PEDAGOGIK INDONESIA - Supriatna, Mamat (PEDAGOGIA, 2016)
Pedagogical discourse in Indonesia is inseparable from the development of the nation's history. Throughout the nation's history, pedagogical discourse in Indonesia remains stagnant as the object of its study is continued to reside on the practical level of education. Academicians, policy makers, observers, and practitioners of education still do not care about foundational and structural objects of the study that contribute to the sturdiness of the scientific foundation and the education system. This paper aims to analytically describe the problem of the ontology of the science education, which focuses on aspects of the scope and boundaries of the research paper. Therefore, this paper is expected to stimulate research and development of science and praxis of education.